ANALISIS KINERJA RUAS JALAN AKIBAT HAMBATAN SAMPING ( STUDI KASUS : Jl. SOEKARNO HATTA PASAR BAWAH KOTA BUKITTINGGI ) - Misbah, Misbah; Hendrizal, Hendrizal (Jurnal Teknologi dan Vokasi, 2023)
Jalan Soekarno Hatta is a secondary collector road with 4 lanes 2 directions divided (4/2 D) as the main road to the trading center of the City of Bukittinggi. Based on the initial observations made, it can be seen that vehicles passing through this road are quite busy, and there are often traffic jams caused by the area being a market area and a shopping center which does not have sufficient parking space so that parking activities use a lot of the road body which causes narrowing. effective road width. The purpose of this research is to find out and analyze the performance of Jalan Soekarno Hatta in terms of traffic volume, capacity and level of service (LOS). While the method used is the 1997 MKJI method by collecting primary data, in the form of road geometric data, traffic volume and side barriers obtained directly at the research location, and secondary data, in the form of population data. Based on the research results, it was obtained that the maximum traffic volume occurred on the main survey, namely on Wednesday for both directions of 518.25 pcu/hour and 522.25 pcu/hour at 11.30 to 12.30 WIB and 11.00 to 12.00 WIB. As for the capacity, the same was obtained at 1148.82 pcu/hour for both directions. Then also the average top speed on the Soekarno Hatta Road section, namely motorbikes with a speed of 20.08 Km/hour in the direction of Janjang 40- Bypass and in the opposite direction from Bypass- Janjang 40 the highest speed is also motorbikes with a speed of 20.20 Km/hour. The side barriers on Jalan Soekarno Hatta are included in the very high side resistance (VH) class category. And in terms of the level of service, Jalan Soekarno Hatta is included in category C where for the classification of the road the flow is fairly smooth, the speed is still controlled, the V/C can still be tolerated. The recommended recommendation is to control the parking area for motorbike riders and provide a special place for city transport cars (angkot) to wait for passengers and install signs that prohibit stopping and signs prohibiting parking.